Impact of friction stir welding on recrystallization of oxide dispersion strengthened ferritic steel. Issue 1 (January 2018) - Han, Wentuo; Liu, Pingping; Yi, Xiaoou; Zhan, Qian; Wan, Farong; Yabuuchi, Kiyohiro; Serizawa, Hisashi; Kimura, Akihiko
Abstract: Oxide dispersion strengthened (ODS) steels can be used as the structural materials in the future fusion reactors and the fuel cladding materials in the advanced fission reactors. However, the weldability of ODS steels is a severe problem. In the present study, defect-free joints of the 15Cr-ODS ferritic steel were achieved by friction stir welding at different rotation speeds. The recrystallization, hardness and tensile properties are highly related with the rotation speed of the stir tool. The higher rotation speed results in coarser grains in the top SZ, while the grain size exhibits more complicated relation with the rotation speed in the SZ center. The joint welded at 250 rpm exhibits a maximum tensile strength of 974 MPa that reaches about 84% of that of the base metal.